Antimicrobial and biological effects of N-diphenylphosphoryl-P-triphenylmonophosphazene-II and di(o-tolyl)-phosphoryl-P-tri(o-tolyl)monophosphazene-III on bacterial and yeast cells - Yilmaz, Ö; Aslan, F; Öztürk, AI; Vanli, NS; Kirbag, S; Arslan, M (Academic Press Inc Elsevier Science, 2002)
The purpose of the study was to synthesize and evaluate the antimicrobial effects of two monophosphazenes, N-diphenylphosphoryl-P-triphenylmonophosphazene-II and N-di(o-tolyl)phosphoryl-P-tri(o-tolyl)monophosphazene-III on bacterial and yeast strains. The biological effects of these molecules were compared with a potential antioxidant vitamin E. According to results, the triphenyl monophosphazene-II has antimicrobial effect on all the bacterial and yeast cells, but tri(o-tolyl)monophosphazene-III has only antimicrobial effect on some bacterial cells. When the concentration of triphenyl monophosphazene-II was raised, it was observed that inhibition zone increased on the bacterial growth media. The biological effects of these molecules were compared to vitamin E in the Saccharomyces cerevisiae culture media. In 200 mug administered culture media, the cell density decreased in vitamin E, triphenyl monophosphazene-II and tri(o-tolyl)monophosphazene-III groups at the end of 24 and 48 h incubation times (p < 0.001, p < 0.05). While the cell densities in vitamin E.
Keywords: triphenyl monophosphazene-II; tri(o-tolyl)monophosphazene-III; antimicrobial and biological effects; vitamin E; bacterial and yeast cells